Current loop-mediated isothermal amplification (LAMP) technologies for the detection of poultry pathogens. Issue 2 (26th February 2018) - EHTISHAM-UL-HAQUE, S.; ZAMAN, M.A.; KIRAN, M.; RAFIQUE, M.K.; QAMAR, M.F.; YOUNUS, M.
Abstract : Traditional diagnostic capabilities (serology and culture) are not enough to monitor the poultry infections efficiently. For effective control of poultry infections, a regular program incorporating simple and cost-effective molecular diagnostics is necessary. On this rationale, it is possible to present working molecular diagnostic technology that would work equally well in field as well as in the laboratory. Recently, the loop-mediated isothermal amplification (LAMP) assay has emerged as simple and inexpensive diagnostic tool for the molecular detection of various animal pathogens. To perform LAMP, no specialised instruments ( e.g. thermal cycler) are required, permitting its use in developing countries. Various reliable LAMP assays have been reported for the detection of different poultry pathogens. However, still there is a need to improve the sensitivity, specificity, reproducibility, user-friendliness, delivery to end-user and affordability of LAMP assays. This article reviews current LAMP assays available for the molecular detection of important viral, bacterial and protozoan pathogens of poultry. It focuses on the various aspects of LAMP for the diagnosis of important poultry pathogens based upon pathogen type, specimen, target genes, LAMP primer types, detection limits, fluorescent detectors and LAMP chemistry used. This paper provides updates on principle, instrumentation, basic methodology, quantification capability, reagents and kits used currently in performing LAMP.